Respuesta :
Given equation: 3(x + 4) + 2 = 2 + 5(x – 4).
First step is to distribute 3 on left side and 5 on right side of the equation, we get
3x + 12 + 2 = 2 + 5x – 20
Second step is combining like terms, 12+2=14 and 2-20=-18.
We get
3x +14 = 5x -18.
Third step, we need to get rid 18 from right side and 3x from left side.
Adding 18 on both sides and subtracting 3x from both sides, gives
32 = 2x.
Fourth step , we need to get rid 2 from right side from 2x.
We need to divide both sides by 2, we get
16=x.
The given equation [tex]3(x+4)+2=2+5(x-4)[/tex] can be simplified using BODMAS rule. The conclusion of the given equation is [tex]16=x[/tex].
Given equation:
[tex]3(x+4)+2=2+5(x-4)[/tex]
First step is to distribute 3 on left side and 5 on right side of the equation,
we get
[tex]3x+12+2=2+5x-20[/tex]
Second step is combining like terms, and .
We get
[tex]3x+14=5x-18[/tex]
Third step, we need to get rid 18 from right side and from left side.
Adding 18 on both sides and subtracting [tex]3x[/tex] from both sides, gives
[tex]32=2x[/tex]
Fourth step , we need to get rid of 2 from the right side 2x.
We need to divide both sides by 2, we get
[tex]16=x[/tex]
For more information:-
https://brainly.com/question/19125604